Congenital cytomegalovirus infection via a re-infected mother with original antigenic sin: A case report. (December 2018) - Koshizuka, Tetsuo; Toriyabe, Kuniaki; Sato, Yuko; Ikuta, Kazufumi; Ikeda, Tomoaki; Suzutani, Tatsuo
Highlights: A case of congenital cytomegalovirus (CMV) infection caused by re-infection during pregnancy is reported. The CMV strains were analyzed using a strain-specific ELISA and qPCR. The child was infected congenitally with a re-infected CMV strain. The mother did not produce antibodies against the re-infected CMV strain. Abstract: A 27-year-old pregnant woman who was positive for anti-cytomegalovirus (CMV) antibodies gave birth to a congenitally CMV-infected neonate at 40 weeks of gestation. According to strain-specific serological analysis, which is able to determine the two types of CMV glycoprotein H (gH), the mother possessed anti-gH(To) antibodies only, but the neonate possessed anti-gH(AD) and anti-gH(To) antibodies at 4 weeks after birth. As the anti-gH(To) IgG was decreased in the neonate at 8 months post-delivery, these antibodies are thought to have been transferred from the mother as maternal antibodies. The anti-gH(AD) IgG level was maintained in the child even after 8 months post-delivery. Congenital infection with a CMV gH(AD) type strain was confirmed by strain-specific real-time PCR using a urine specimen from the child. On the other hand, anti-gH(AD) IgG was not detected even after 8 months post-delivery in a maternal specimen. The mother only produced antibodies against the CMV strain identified as the primary infection, which is characteristic of original antigenic sin.